Efisiensi Alokasi Material dan Notifikasi Vendor dengan Shipping Notification: Studi Kasus - Riyyan Adiputra Sabar Kristianto; Siana Halim (Jurnal Titra, 2021)
The materials' delivery delay at a manufacturer's industry causes problems in the production line. The Purchasing Department must notify the vendors whose deliveries are late based on the delivery notification to minimize the product expenses. This research aims to construct material allocation methods and group the vendors to notify the vendors of the shipping materials. We started with mining the SAP data and then cleaning the dataset and constructing the algorithm using Python to create a shipping notification. Finally, we presented the results in a dashboard built using Power BI. As the result of this study, we have two material allocation groups: the high-quantity and the high-value method. Additionally, we also group the purchase orders (PO) as problem-free purchase orders and purchase orders with problems. Based on those grouping in material allocation and purchase orders; we classified the jobs as a job with complete required materials (Job OK), a job with uncomplete required materials (Job Not OK), and a job that the needed materials are on the way and the vendors can be notified to speed up the delivery (Job may be OK).  This classification helps the Purchasing Department send notifications to the vendors who potentially have materials delivery delays.